Anti-Corruption Laws And Public Administration Reform - Sahri (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This article explores the legal dimensions of anti-corruption and public administration reform in post-conflict states as essential pillars for rebuilding institutional integrity and sustaining peace. In the aftermath of violent conflict, corruption often thrives in the vacuum of weakened institutions, undermining efforts toward recovery, legitimacy, and development. Using a comparative legal analysis approach, this study examines the effectiveness of legal frameworks—including anti-corruption statutes, independent oversight bodies, public procurement regulations, and whistleblower protection laws—in promoting good governance and restoring public trust. Focusing on selected post-conflict countries in Sub-Saharan Africa and Southeast Asia, the article evaluates how legal reform initiatives are influenced by both international norms, such as the United Nations Convention against Corruption (UNCAC), and local political realities. It highlights the implementation gap between legal commitments and practice, identifying structural constraints such as limited judicial capacity, political interference, and under-resourced oversight institutions. The analysis finds that legal strategies must move beyond punitive enforcement to incorporate preventive and participatory mechanisms that empower civil society, enhance transparency, and institutionalize accountability. The article concludes that sustainable anti-corruption reform in post-conflict settings requires a context-sensitive, rights-based approach aligned with Sustainable Development Goal 16. Legal reforms must not only criminalize corruption but also establish resilient governance systems that uphold the rule of law and democratic accountability.